DEVELOPMENT OF A MOODLE QUIZ AS A MATHEMATICS ASSESSMENT TOOL FOR GRADE VIII STUDENTS OF SMP NEGERI 1 KOLAKA - Nurafni, A Dwi; Nasrum, Akbar; Jahring, Jahring (JME (Journal of Mathematics Education), 2025)
This study aims to develop a digital-based mathematics assessment tool using the Moodle application for Grade VIII students at SMP Negeri 1 Kolaka, in response to the growing need for effective and accessible digital testing platforms in mathematics education. The development process followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which supports a systematic and iterative approach to instructional design. The research involved 30 students from Class VIII D, selected through purposive sampling. Content validity was evaluated by two subject-matter experts using a structured rubric, resulting in an average score of 93% (very valid). Media validity was assessed by a media expert, yielding an average score of 82% (very valid). The practicality of the instrument was examined through student questionnaires focusing on usability and clarity, achieving an average score of 84%, indicating high practicality. These results suggest that the Moodle-based quiz is a valid and practical tool for mathematics assessment in junior high schools, with potential to enhance digital assessment practices in similar educational settings.